(untitled) (Annals of Medical Research, 2021)
Aim: It is known that early prediction of the patients who may develop contrast-induced is nephropathy (CIN) and initiate prophylactic treatment to reduce the risk of morbidity-mortality, hospitalization and prolonged length of stay. In our study, we aimed to compare the Zwolle, Cadillac and Syntax 2 (SS-2) risk scores that are currently used in the management of and predict mortality in patients with ST elevation myocardial infarction (STEMI) in terms of predicting CIN development.Material and Methods: We enrolled 1622 patients who were diagnosed as STEMI and underwent primary coronary angiography between July 2014 and December 2018. 1381 patients were taken to the final analysis and two groups; CIN - (n=1295) and CIN + (n=86) were formed. Risk scores were compared in terms of CIN prediction.Results: The mean age of the patients was 62±8 years and 72% of them were males. SS-2, Zwolle and Cadillac scores were significantly higher in CIN+ group (all p values 0.001). A comparative ROC curve analysis was performed for the estimation and clinical use of CIN. In the ROC curve analysis, the cut-off value for SS-2 was 16.7 (AUC:0.82) with a sensitivity of 80.1% and a specificity of 58%. The cut-off value for Cadillac was 1.5 (AUC:0.80), 78% sensitivity and 58% specificity. For Zwolle, the cut-off value was 2.5 (AUC:0.75) and the sensitivity was 73% and the specificity was 69%.Conclusions: CIN, which develops after coronary angiography in STEMI patients, causes an increase in morbidity and mortality. The risk scores used in STEMI patients, in particular SS-2, may be more useful in predicting the development of CIN than in the Zwolle and Cadillac scores.Keywords: Zwolle; Cadillac; Syntax 2 score; contrast induced nephropathy.